Constraints And Opportunities For Cultivation Of Moringa oleifera In The Zimbabwean Smallholder Growers - Mudyiwa, SM; Gadzirayi, CT; Mupangwa, JF; Gotosa, J; Nyamugure, T (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study sought to establish the constraints to Moringa agronomic practices and marketing in the smallholder farming sector of Zimbabwe. Purposive sampling selected 96 respondents across four study districts in Zimbabwe who were interviewed using an open-ended questionnaire. Eight focus group discussions disaggregated by gender were carried out to supplement primary data. Growers asserted Moringa oleifera production problems of livestock damage, theft, seed supply, inefficient cultivation practices resulting in inherent low productivity and poor marketing. The growers coped through intensive monoculture of M. oleifera, enhanced local seed supply from establishing their own seed orchards, product value addition and organized associations. Moringa can be used to promote climate change resilient agricultural systems and will be a solution to environmental problems. Int. J. Agril. Res. Innov. & Tech. 3 (1): 12-19, June, 2013 DOI: http://dx.doi.org/10.3329/ijarit.v3i1.16044